PHYLOGENY OF FOUR DINOPHYSIACEAN GENERA (DINOPHYCEAE, DINOPHYSIALES) BASED ON rDNA SEQUENCES FROM SINGLE CELLS AND ENVIRONMENTAL SAMPLES(1) - Handy, Sara M (Journal of phycology, 2009)
© 2009 Phycological Society of America.